GENDERED AND RACIALIZED LANGUAGE IN GRACE M. CHO’S TASTES LIKE WAR: A FEMINIST STYLISTIC ANALYSIS - Mujaddidah, Husnul; Agus, Sitti Hasmah; Harun, Muhammad; Yudith, Madeline (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This study investigates how gendered and racial meanings are constructed through word-level language choices in Grace M. Cho’s memoir Tastes Like War (2021) using a feminist stylistic approach. Drawing on Sara Mills’ theory of gendered representation and evaluative language, supported by insights from Robin Lakoff and Dale Spender, the researcher examines how naming practices, evaluative adjectives, and role descriptions position female characters within patriarchal and racialized discourses. The study employs a descriptive qualitative method based on close textual reading and lexical analysis. The primary data consist of words, phrases, and expressions referring to female characters, particularly Cho’s mother, while secondary data include feminist stylistic scholarship and related studies on memoir and gender. The findings show that Kongja is frequently identified through relational and ethnic labels, while evaluative adjectives and prescriptive expressions frame her within norms of motherhood, domesticity, and female vulnerability. Pathologizing and racialized terms further construct deviation from ideal femininity as abnormal or stigmatized. At the same time, the memoir strategically reuses patriarchal language with ironic distance, exposing and questioning the ideological judgments imposed on immigrant womanhood. The study concludes that feminist stylistics is an effective framework for revealing how memoir language both reproduces and critiques gendered and racialized constructions of women’s identities.Keywords: feminist stylistics, naming